Trend in eating habits among Lithuanian school-aged children in context of social inequality: three cross-sectional surveys 2002, 2006 and 2010 - Zaborskis Apolinaras; Lagunaite Reda; Busha Ryan; Lubiene Jolita (BMC, 2012)
Abstract Background Intermittent monitoring of food intake at the population level is essential for the planning and evaluation of national dietary intervention programs. Social-economic changes in Lithuania have likely affected dietary habits, but only a limited number of temporal studies on food intake trends among young population groups have been published. The aim of this study was to investigate changes in eating habits among Lithuanian school-aged children from 2002 to 2010, and to explore the association of these changes with the respondents' reported socio-economic status (SES). Methods We used Lithuanian data from the cross-national Health Behaviour in School-aged Children (HBSC) study collected in 2002, 2006 and 2010. Analyses were conducted on comparable questionnaire-based data from children aged 11, 13 and 15 (total n = 17,189) from a random sample of schools. A food frequency questionnaire was used to investigate frequencies of food consumption. Logistic regression was used to examine the affects of changing social variables on reported diet trends. Results In Lithuania, school-aged children have low intakes of fruits and vegetables. Only 21.1% of boys and 27.1% of girls reported daily fruit consumption. Similarly, 24.9% of boys and 29.6% of girls disclosed vegetable intake at least once daily. Comparing 2010 to 2002, the proportion of girls who consumed fruits daily increased from 24.2% to 31.0% (p < 0.001) but the proportion of boys who consumed vegetables daily decreased from 29.3% to 23.1% (p < 0.001). In 2006, for both sexes, there were observed increases in regular (at least five days a week) intake of sweets and chocolates, biscuits and pastries, and soft drinks; however, in the next survey (2010) these figures decreased. In addition, between 2006 and 2010, a substantial decrease in regular consumption of chips and fast food was also detected. Fruit and vegetable consumption as well as intake of sweets and chocolates, biscuits and pastries and soft drinks increased with family social-economic status and family material wealth. Trends in consumption of fruits, and other foods, and their association with changing social variables were demonstrated using the ORs estimated by three logistic models, using 2002 as the reference point. Changes in social variables from 2002 to 2010 affected the likelihood of daily consumption of fruits among boys by 22.5% (the corresponding OR decreased from 1.11 to 0.86) and among girls by 34.0% (the corresponding OR decreased from 1.41 to 1.12). Over the study period, changing social variables had little impact on the daily consumption of vegetables and other foods. Conclusions Based on the food consumption trends observed in Lithuania, increases in consumption of fruits and vegetables should be promoted, along with a reduction in the intake of less healthy choices, such as soft drinks and high-fat, high-sugar snack foods, by diminishing social inequalities in food consumption.